Human telomeric RNA G-quadruplex response to point mutation in the G-quartets - Agarwala, Prachi; Kumar, Santosh; Pandey, Satyaprakash; Maiti, Souvik (Journal of Physical Chemistry B, 2015)
Many putative G-quadruplex forming sequences have been predicted to exist in the human genome and transcriptome. As these sequences are subject to point mutations or SNPs (single nucleotide polymorphisms) during the course of evolution, we attempt to understand impact of these mutations in context of RNA G-quadruplex formation using human telomeric RNA (TERRA) as a model sequence. Our studies suggest that G-quadruplex stability is sensitive to substitution of the guanines comprising G-quartets. While central G-quartet plays a crucial role in maintaining the DNA G-quadruplex stability as evident in literature, there is equal importance of three G-quartets in the stability of RNA quadruplex structure. The work here highlights the alterations in the G-quartet are detrimental to the integrity of overall RNA G-quadruplex structure. Furthermore, TmPyP4 molecules are shown to exhibit similar binding behavior toward telomeric RNA G-quadruplex harboring base substitutions employing CD titrations and isothermal titration calorimetry; well indicating that mutation does not influence TmPyP4 recognition ability as it affects the stability of RNA G-quadruplex. Thus, our study implicates that mutation in G-quartets causes destabilization of RNA G-quadruplex without affecting its trans factor binding ability.